Faktor-Faktor Yang Mempengaruhi Keputusan Konsumen Dalam Membeli Sayuran Hidroponik Di Galery Hidroponik Aceh Kecamatan Lhoknga Kabupaten Aceh Besar - Hilda, Cut Mutia; Khumaira, Khumaira; Fitri, Sri (Serambi Saintia : Jurnal Sains dan Aplikasi, 2024)
Vegetables are one of the elements of food that are healthy and important for the body. The benefits of consuming vegetables every day for body health are due to the high content of various vitamins and minerals, one of which is hydroponic vegetables. The aim of this research is to determine the factors that have a relationship with consumer decisions in purchasing hydroponic vegetables in the Aceh Hydroponic Gallery, Lhoknga District, Aceh Besar Regency. The research method used is the survey method. The sampling technique used was determined purposively (intentionally) with a sample size of 30 respondents. The data analysis model used is the Spearman Rank correlation test analysis. Based on the research results, cultural factors in the high category amounted to 43.4%, social factors in the low category amounted to 86.7%, and personal factors in the medium category amounted to 63.3%. The correlation results show that the cultural factor is 0.445*, with a sig (2-tailed) value of 0.014 or 0.05. This means that the level of strength of the relationship between cultural factors and the decision to purchase hydroponic vegetables is moderate. The social factor is 0.217, with a sig (2-tailed) value of 0.249 or 0.05. This means that the level of strength of the relationship between social factors and the decision to purchase hydroponic vegetables is low. The factor is 0.775, with a sig (2-tailed) value of 0.000 or 0.05. This means that the level of strength of the relationship between personal factors and the decision to purchase hydroponic vegetables is high.Keywords: Hydroponics,  Buying Decision, Vegetable